THE DISPUTE SETTLEMENT OF PROCUREMENT LAND DETERMINATION COMPENSATION (Study on the Law Number 2 Year 2012 on Land Procurement for Public Interest Development) - Hamdi Hamdi (Fakultas Hukum Universitas Mataram, 2014)
Procurement of land for development for common interest should be implemented based on the principles of humanity, expedience, certainty, transparency, agreement, participation, livelihoods, sustainable and alignment. With this principle is applied to the implementation of the land acquisition can minimized occurrence the conflict in land acquisition. Providing the compensation on holders of land rights is feasible and equitable, viable and feasible in terms of the amount of the gift means that holders of land rights do not feel forced to relinquish their land primarily used for the development interest based on respect on holder rights. Deliberation in the land acquisition done as much as possible and remain in a neutral position and remained on the same level and no one is feeling pressured or forced, perinsip respect for the holders of land rights set forth in the Acts Number 2 Year 2012 to provide the legal protection and in providing the compensation no cause the land rights holders no worse its condition than before the release of land rights. Keywords: compensation, land acquisition, public interest